(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
Fuzzy set theory, extensively applied in several fields, has been recognized as a powerful tool in dealing with the knowledge of imprecision due to its ability in representing uncertainty and vagueness mathematically. In fuzzy data analysis, searching for a general measure that can effectively and efficiently rank fuzzy numbers for critical information revelation and decision-making has well attracted the special attention of numerous scholars. Several approaches have been proposed up to date; however, their certain shortcomings spare capacity for enhancement. In this paper, an innovative ranking index incorporating three key components such as left-right areas, expectation value of centroid, and level of optimism is proposed. Through numerically comparative studies thorough with current major ranking methods, our approach demonstrates a significant improvement in terms of ranking robustness and discrimination power.